Audit of Helicobacter pylori Testing in Microbiology Laboratories in England: To Inform Compliance with NICE Guidance and the Feasibility of Routine Antimicrobial Resistance Surveillance - Rosalie Allison; Donna M. Lecky; Megan Bull; Kim Turner; Gauri Godbole; Cliodna A. M. McNulty (International Journal of Microbiology)
Introduction. The National Institute for Health and Clinical Excellence (NICE) guidance recommends that dyspeptic patients are tested for Helicobacter pylori using a urea breath test, stool antigen test, or serology. Antibiotic resistance in H. pylori is globally increasing, but treatment in England is rarely guided by susceptibility testing or surveillance. Aims. To determine compliance of microbiology laboratories in England with NICE guidance and whether laboratories perform culture and antibiotic susceptibility testing (AST). Methods. In 2015, 170 accredited English microbiology laboratories were surveyed, by email. Results. 121/170 (71%) laboratories responded; 96% provided H. pylori testing (78% on site). 94% provided H. pylori diagnosis using stool antigen; only four provided serology as their noninvasive test; 3/4 of these encouraged urea breath tests in their acute trusts. Only 22/94 (23%) of the laboratories performed H. pylori cultures from gastric biopsies on site; 9/22 performed AST, but the vast majority processed less than one specimen/week. Conclusions. Only five laboratories in England do not comply with NICE guidance; these will need the guidance reinforced. National surveillance needs to be implemented; culture-based AST would need to be centralised. Moving forward, detection of resistance in H. pylori from stool specimens using molecular methods (PCR) needs to be explored.